2014
DOI: 10.1021/ja5003197
|View full text |Cite
|
Sign up to set email alerts
|

Low pH Electrolytic Water Splitting Using Earth-Abundant Metastable Catalysts That Self-Assemble in Situ

Abstract: Typical catalysts for the electrolysis of water at low pH are based on precious metals (Pt for the cathode and IrO2 or RuO2 for the anode). However, these metals are rare and expensive, and hence lower cost and more abundant catalysts are needed if electrolytically produced hydrogen is to become more widely available. Herein, we show that electrode-film formation from aqueous solutions of first row transition metal ions at pH 1.6 can be induced under the action of an appropriate cell bias and that in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 59 publications
5
120
1
Order By: Relevance
“…Firstly, spinel Co 3 O 4 intrinsically has mixed oxidation states of Co 2þ and Co 3þ , which are considered as the active centers for OER in the Co 3 O 4 architectures. In accordance with the prediction from Pourbaix diagram of cobalt [52] and previous results of XAS [8,53], in situ Raman spectroscopy [9] and theoretical calculations [54,55], the Co 2þ in Co 3 O 4 would be oxidized to the catalytically active cobalt species Co 3þ / 4þ , which are particularly critical to enable OER. Secondly, the Co 3 O 4 architectures present hierarchically porous structure and high specific surface area.…”
Section: Resultssupporting
confidence: 87%
“…Firstly, spinel Co 3 O 4 intrinsically has mixed oxidation states of Co 2þ and Co 3þ , which are considered as the active centers for OER in the Co 3 O 4 architectures. In accordance with the prediction from Pourbaix diagram of cobalt [52] and previous results of XAS [8,53], in situ Raman spectroscopy [9] and theoretical calculations [54,55], the Co 2þ in Co 3 O 4 would be oxidized to the catalytically active cobalt species Co 3þ / 4þ , which are particularly critical to enable OER. Secondly, the Co 3 O 4 architectures present hierarchically porous structure and high specific surface area.…”
Section: Resultssupporting
confidence: 87%
“…These films mediate water oxidation to O 2 at pHs above 3.5, but at lower pHs these films dissolve to give soluble Co(II) species which mediate water oxidation to H 2 O 2 . 28 Bloor et al subsequently showed that both a Co-oxide water oxidation catalyst and a Co-metal based proton reduction catalyst could be electrodeposited simultaneously from the same electrolyte bath (0.2 M Co 2 (PO 4 ) 3 at pH 1.6) under an applied bias, and that these catalysts were functionally stable for the two half reactions of water splitting for as long as the potential difference across the cell was at least 2 V. 29 Moreover, the authors were able to demonstrate that these electrodeposited catalysts were metastable at pH < 2, and that if the circuit was opened the films redissolved into the electrolyte bath with concomitant O 2 and H 2 evolution (see Figure 2) 2 and H 2 production during electrolysis (when a potential was applied) was below unity, full Faradaic efficiency for the production of both gases was obtained upon complete dissolution of the films. This work served to highlight the ability of first row transition metals to mediate heterogeneous electrolytic water splitting in acidic media by exploiting, rather than trying to avoid, the natural propensity of electrodeposits of these metals to dissolve at low pH.…”
Section: Electrodeposited Catalysts For Water Oxidation Based On Cobaltmentioning
confidence: 99%
“…Splitting water into hydrogen and oxygen to store light or electric energy in the form of chemical bonds has stimulated intense research due to accelerated depletion of fossil fuels [1][2][3][4][5] . The water-splitting reaction can be divided into two half-reactions: the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), both of which are crucial for the overall efficiency of water splitting 6-8 .…”
Section: Introductionmentioning
confidence: 99%